Synthesis, characterization and thermal behavior of complexes of Cu(II), Zn(II) and Cd(II) with S,S '-methylenebis(cysteine) - Cavicchioli, M.; Corbi, P. P.; Melnikov, P.; Massabni, Antonio Carlos [UNESP] (Taylor & Francis Ltd, 2002)
Synthesis and characterization, including data on thermal decomposition, are reported for the complexes of S,S'-methylenebis(cysteine) (djenkolic acid) with copper(II), zinc(II) and cadmium(II): CuC(7)H(12)N(2)O(4)S(2) [I]; ZnC(7)H(12)N(2)O(4)S(2) [II] and CdC(7)H(12)N(2)O(4)S(2) [III] X-ray diffraction showed that the compounds are isostructural and belong to a monoclinic system. According to IR spectra, COO, NH(2) groups and bridging sulfur atoms are the main coordination sites.
Keywords: S,S '-methylenebis(cysteine); djenkolic acid; transition metals; complexes